What factors influence the presence of women in family business governance? - Chamochumbi Diaz, Gail Denisse; Cesaroni, Francesca Maria; Sentuti, Annalisa (Piccola Impresa / Small Business, 2019)
The aim of this paper is to investigate the woman involvement in family business governance. The empirical analysis focus on 233 Italian family business, studied during the time-frame 2007-2014. The variables investigated are related to the factors able to hinder or foster the woman presence in the firm’s governance. Findings show that the woman presence in the family firm’s board is influenced by belonging to the owner family, by the generational stage of the firm and by the average age of directors.